math help !!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!
Use point-slope formula:
y - y1 = m(x - x1)
y - (-4) = 2 (x - 1)
y + 4 = 2x - 2
y = 2x - 6
math help !!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!
Use point-slope formula:
y - y1 = m(x - x1)
y - (-4) = 2 (x - 1)
y + 4 = 2x - 2
y = 2x - 6
point-slope form is: y = mx + b
We're given the slope, m = 2, so: y = 2x + b
We're also given it goes through (1, -4) and those are x and y, since points are given as (x, y).
Replace the y and x in:
y = 2x + b with -4 and 1:
-4 = 2(1) + b subtract 2 from sides
-4 - 2 = 2(1) + b - 2
-6 = b
Now we know b is -6, can finish the equation y = 2x + b as
y = 2x - 6